Strategies in Learning English of the Non English Education Study Program - larasati, desty (Universitas Nurul Jadid, 2025)
PAUD (Early Childhood Teacher Education) Study Program at the Faculty of Teacher Training and Education, Sriwijaya University—students who are not from an English education background. A quantitative descriptive method was used, involving a total population of 163 students from the 4th and 6th semesters who had completed English courses. Data were collected using the Strategy Inventory for Language Learning (SILL) version 7.0 by Oxford (1990), which categorizes strategies into memory, cognitive, compensation, metacognitive, affective, and social. The findings revealed that the most frequently used strategies were metacognitive, memory, and affective, indicating strong internal motivation, reflection, and emotional regulation. Meanwhile, cognitive, compensation, and social strategies were moderately applied. The results suggest that PG-PAUD students predominantly rely on internal, self-directed strategies to learn English, while social interaction and adaptive communication strategies are less frequently employed. These findings contribute to the understanding of English learning among non-English majors and highlight the importance of promoting balanced strategy use in language instructionThis study aims to explore the English language learning strategies employed by students of the PG-